Free abelian dimonoids - Zhuchok, Y. (Algebra and Discrete Mathematics, 2015)
We construct a free abelian dimonoid and describe the least abelian congruence on a free dimonoid. Also we show that free abelian dimonoids are determined by their endomorphism
semigroups.